2001
DOI: 10.1080/07315724.2001.10719034
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antioxidant Effects of Zinc and Chromium Supplementation in People with Type 2 Diabetes Mellitus

Abstract: These data suggest the potential beneficial antioxidant effects of the individual and combined supplementation of Zn and Cr in people with type 2 DM. These results are particularly important in light of the deleterious consequences of oxidative stress in people with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
2
10

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(200 citation statements)
references
References 27 publications
14
174
2
10
Order By: Relevance
“…It has been reported that GSH, various antioxidant vitamins and compounds, trace elements such as vitamins C and E, flavanoids, saponins, vanadium, and selenium prevent the increase of tissue NEG levels. 44) We found a reduction of the NEG increase in the tissues of the animals to which chard extract was administered, producing a significant decrease in the diabetic group. Lipid peroxidation has been implicated in the pathogenesis of many degenerative disorders, including chemically induced diabetes.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that GSH, various antioxidant vitamins and compounds, trace elements such as vitamins C and E, flavanoids, saponins, vanadium, and selenium prevent the increase of tissue NEG levels. 44) We found a reduction of the NEG increase in the tissues of the animals to which chard extract was administered, producing a significant decrease in the diabetic group. Lipid peroxidation has been implicated in the pathogenesis of many degenerative disorders, including chemically induced diabetes.…”
Section: Discussionmentioning
confidence: 76%
“…No unpublished studies were found. Fourteen studies were excluded because they were either not randomized, double-blind and placebocontrolled, [31][32][33][34][35] did not test a monopreparation of chromium picolinate, [36][37][38][39][40] did not report on body weight [41][42][43] or were published in duplicate. 44 Ten trials met all inclusion criteria and provided data for body weight that were suitable for statistical pooling (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A significant decrease in Zn++ and Se++ levels in whole blood has been reported in diabetic pregnancy (24,25,26), compared to normoglycemic pregnancy. The potential beneficial effects of Zinc and Chromium have been reported in patients with type 2 diabetes mellitus (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%